1989
DOI: 10.1128/jb.171.10.5747-5749.1989
|View full text |Cite
|
Sign up to set email alerts
|

Timing of spoII gene expression relative to septum formation during sporulation of Bacillus subtilis

Abstract: spoII mutants formed heat-resistant spores when transformed with spo+ DNA near the start of sporulation. Many of the spores formed remained genetically spoIl. It is deduced from this result and previous epistasis experiments that the spoIl loci are transcribed before the spore septum is formed.Formation of the asymmetrically sited sporulation septum is a crucial event in spore formation. A series of genetic loci, the spoIlI loci, are defined by mutations that permit formation of the spore septum but prevent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 14 publications
4
69
0
1
Order By: Relevance
“…In the t 1:5 sample, more than half of the cells with detectable j F (39% of total cells) were at the preseptation stage (Table 1). This was in accordance with previous direct and indirect experiments showing that induction of the spoIIA operon, encoding j F , occurs before septation (Gholamhoseinian & Piggot 1989;Partridge & Errington 1993;Bylund et al 1994). From t 1.5 to t 3 the proportion of pre-septational cells containing j F decreased, and the number of postseptational cells increased concomitantly.…”
Section: Immunofluorescence Methods and Analysis Of The Fluorescencesupporting
confidence: 92%
“…In the t 1:5 sample, more than half of the cells with detectable j F (39% of total cells) were at the preseptation stage (Table 1). This was in accordance with previous direct and indirect experiments showing that induction of the spoIIA operon, encoding j F , occurs before septation (Gholamhoseinian & Piggot 1989;Partridge & Errington 1993;Bylund et al 1994). From t 1.5 to t 3 the proportion of pre-septational cells containing j F decreased, and the number of postseptational cells increased concomitantly.…”
Section: Immunofluorescence Methods and Analysis Of The Fluorescencesupporting
confidence: 92%
“…However, shortly thereafter, it became clear that the third gene in the operon, spoIIAC, encoded a product that was homologous to an RNA polymerase factor (62,274), named F (183). The first targets identified for E-F action were spoIIIG and gpr (282,285), and the site of expression of spoIIIG was shown to be the prespore (93,142,189), as it has been for all E-F -directed genes analyzed subsequently (231).…”
Section: Activation Of F Spoiia Operonmentioning
confidence: 99%
“…Although the spoIIA operon is expressed prior to asymmetric division (93,218), F does not become active until after asymmetric division (93,142). It seemed likely that F was subject to some form of posttranslational regulation, and genetic analysis revealed that the other two products of the spoIIA operon, SpoIIAA and SpoIIAB, regulate its activity.…”
Section: Posttranslational Regulation Of Fmentioning
confidence: 99%
“…The F factor is synthesized shortly after the onset of sporulation in the predivisional sporangium (Gholamhoseinian and Piggot 1989). It does not become active in directing gene transcription, however, until after asymmetric division, when its activity is confined to the forespore (Margolis et al 1991).…”
mentioning
confidence: 99%